2005
DOI: 10.1152/ajpregu.00756.2004
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin is an orexigenic and metabolic signaling peptide in the arcuate and paraventricular nuclei

Abstract: Ghrelin is a 28-amino acid acylated peptide and is the endogenous ligand for the growth hormone secretagogue receptor (GHS-R). The GHS-R is expressed in hypothalamic nuclei, including the arcuate nucleus (Arc) where it is colocalized with neuropeptide Y (NPY) neurons. In the present study, we examined the effects of ghrelin on feeding and energy substrate utilization (respiratory quotient; RQ) following direct injections into either the arcuate or the paraventricular nucleus (PVN) of the hypothalamus. Ghrelin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
90
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(104 citation statements)
references
References 70 publications
11
90
1
2
Order By: Relevance
“…A microinjection of ghrelin into the PVN or ARC increases food intake and RQ in rats (Currie et al 2005). Since the PVN and ARC express GHS-R1a (Zigman et al 2006), these findings together with our present results may indicate that ghrelin directly activates GHS-R1a in the PVN and ARC and induces a suppressive effect on the sympathetic nervous system innervating BAT.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…A microinjection of ghrelin into the PVN or ARC increases food intake and RQ in rats (Currie et al 2005). Since the PVN and ARC express GHS-R1a (Zigman et al 2006), these findings together with our present results may indicate that ghrelin directly activates GHS-R1a in the PVN and ARC and induces a suppressive effect on the sympathetic nervous system innervating BAT.…”
Section: Discussionsupporting
confidence: 79%
“…5-10 nmol for i.v. administration (Nakazato et al 2001, Date et al 2002, Currie et al 2005. We also administered rat des-acyl ghrelin (Peptide Institute, Inc.), which does not bind to GHS-R1a, at a dose of 500 pmol for i.c.v.…”
Section: Microdialysis Of Noradrenaline In Batmentioning
confidence: 99%
See 1 more Smart Citation
“…Circulating ghrelin levels as well as gastric ghrelin mRNA expression have been reported to increase after fasting and decrease rapidly after refeeding (Tschop et al, 2000). Ghrelin stimulates eating when injected into the arcuate and paraventricular nuclei (Currie et al, 2005), and we have shown here that ghrelin resets the SCN clock when applied directly to SCN tissue during the subjective day. Moreover, gastric ghrelin has been found to affect gastric per1 and per2 expression, suggesting that it can also be considered as a signal regulating peripheral oscillators .…”
Section: Discussionsupporting
confidence: 55%
“…Besides the SCN, the arcuate nuclei (Mistlberger and Antle, 1999), the paraventricular nuclei (Kalra et al, 1999;Currie et al, 2005), the dorsomedial hypothalamus (Gooley et al, 2006;Landry et al, 2006), and the digestive system (Davidson et al, 2003) have also been suggested to be important for food entrainment.…”
Section: Introductionmentioning
confidence: 99%